Teacher Difficulties in Teaching Vocabulary - Suardi Suardi; Juwita Eka Sakti (Institut Agama Islam Negeri Palopo, 2019)
This research aims at finding out the teacher difficulties in teaching vocabulary at MTS Batusitanduk. The scope of the research was limited to focus on describing or exploring the difficulties faced by the teacher in teaching English vocabulary. This research applied descriptive qualitative method. The subject of this research was 2 English teachers of MTS Batusitanduk. The research used interview to collect the data. Based on the result of data analysis the research concludes that teacher’s difficulties in teaching vocabulary are difficult in selecting vocabulary to be taught because there are many words in English and the students do not have same ability, difficult in implementing teaching technique or presenting new vocabularies because when presenting the new vocabulary. The students do not pay attention to the teacher’s explanation, noisy, and the students are passive in vocabulary learning. And the teachers are difficult to review or evaluating the students’ understanding about the words that have been taught because the students do not still understand about meaning of the vocabulary.